Holding procedure of Elementary Teaching Methodology workshops Based on the Views of the Faculty of Kerman University of Medical Sciences participating in the workshops - Esmat Nouhi; Ashraf Adhami; Aliakbar Haghdoost (Kerman University of Medical Sciences, 2005)
Background: Teaching Methodology workshop aimed at development of education therefore it must offer the best developed methods of teaching Objectives: To determine the quality of the teaching methodology workshops held in Kerman University of Medical Sciences based on the views of the participators Methods: The views of all 171 faculty members participated in six teaching methodology workshops were evaluated using the questionnaire approved by The Ministry of Health and Medical Education The questionnaire consisted of two sections: demograophic features & statements on the views based on a 5 Likert scale (from strongly agree to strongly disagree) Its validity was 09 measured by the views of experts  Findings: 673 percent of the participators were male and assistant professors 624% 697% of the participants were strongly agreed or agreed upon the statements The most agreement was on proper planning of aims (84%) then giving introductory information in the beginning (81%) sequential outline (82%) respectively The least agreement was found on the facilities (404%) enough time allocated to individual & group discussion (472%) A significant difference was observed between the views based on different workshop sessions (P